A multiscale micromechanical model of needlepunched nonwoven fabrics. (1st October 2016) - Martínez-Hergueta, F.; Ridruejo, A.; González, C.; LLorca, J.
Abstract: A constitutive model for the mechanical behavior of a mechanically-entangled nonwoven fiber network is presented. The model is built upon a detailed characterization of the dominant deformation and failure mechanisms at different length scales (fiber, bundle, network) (Martínez-Hergueta et al., 2015) and accounts for the effects of non-affine deformation, anisotropic connectivity induced by the entanglement points, fiber uncurling and re-orientation as well as fiber disentanglement and pull-out from the knots. The model provides the constitutive response for a mesodomain of the fabric corresponding to the volume associated to a finite element and is divided in two blocks. The first one is the network model which establishes the relationship between the macroscopic deformation gradientF and the microscopic response obtained by integrating the response of the fibers in the mesodomain. The second one is the fiber model, which takes into account the deformation features of each set of fibers in the mesodomain, including non-affinity, uncurling, pull-out and disentanglement. As far as possible, a clear physical meaning is given to the model parameters, so they can be identified by means of independent tests. The numerical simulations based on the model were in very good agreement with the experimental results of the tensile deformation of a commercial needle-punched nonwoven fabric along two perpendicular orientations in terms of the nominal stress–strain curve (including the large anisotropy in stiffness and strength), the specimen shape and the evolution of the fiber orientation distribution function with the applied strain.